Levels of polychlorinated dibenzo-p-dioxins, dibenzofurans (PCDD/Fs) and biphenyls (PCBs) in blood of informal e-waste recycling workers from Agbogbloshie, Ghana, and controls. (June 2015) - Wittsiepe, Jürgen; Fobil, Julius N.; Till, Holger; Burchard, Gerd-Dieter; Wilhelm, Michael; Feldt, Torsten
Abstract: The formation and environmental release of highly toxic organohalogen compounds associated with informal recycling of waste electric and electronic equipment (e-waste) is a growing problem at e-waste dumps/recycling sites (EWRSs) in many developing countries worldwide. We chose a cross-sectional study design to measure the internal exposure to polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) as well as polychlorinated biphenyls (PCBs) of individuals working on one of the largest EWRSs of Africa, located at Agbogbloshie, Accra, Ghana, and in controls from a suburb of Accra without direct exposure to EWRS activities. In whole blood samples of 21 age matched male exposed individuals (mean age: 24.7 years, SD 6.0) and 21 male controls (mean age: 24.4 years, SD 5.7) 17 PCDD/F congeners were determined. Moreover three indicator PCB congeners (#138, #153 and #180) were measured in blood of 39 exposed (mean age: 27.5 years, SD 11.7) and 19 non-exposed (mean age: 26.8 years, SD 9.7) patients. Besides a health examination, biometric and demographic data, residential and occupational history, occupational exposures and working conditions were recorded using a standardized questionnaire. In the exposed group, median PCDD/F-concentrations were 6.18 pg/g lipid base WHO2005 -TEq (range: 2.1–42.7) and significantly higher compared to the control group with 4.60 pg/g lipid base WHO2005 -TEq (range: 1.6–11.6). Concentrations were different for 2, 3, 7, 8-TetraCDD, three HexaCDD and all 10 PCDF congeners, indicating a combustion pattern. Using a multivariate regression analysis exposure to EWRS activities was the most important determinant for PCDD/F exposure. Median PCB levels for the indicator congeners #138, #153 and #180 were 0.011, 0.019 and 0.008 μg/l whole blood (ranges: 0.002–0.18, 0.003–0.16, 0.002–0.078) in the exposed group and, surprisingly, significantly higher in the controls (0.037, 0.062 and 0.022; ranges: 0.005–0.46, 0.010–0.46, 0.004–0.21). In a multivariate regression approach e-waste related activities had no positive influence on internal PCB exposure, but rather the time living in Accra. The internal PCB exposure is in particular notable for a country where PCBs have historically never been produced or used. The impact of EWRS activities on organohalogen compound exposure of individuals working at and living in the surroundings of the Agbogbloshie EWRS, and the surprisingly high PCB exposure of people living in Accra not involved in e-waste activities require further investigation. Highlights: First study on exposure to PCDD/Fs and PCBs from an African informal e-waste site First study on blood levels of PCDD/Fs of directly exposed e-waste workers worldwide E-waste activities were associated with increased internal PCDD/F exposure. Internal PCB exposure of the controls was higher than of the workers. Internal PCB exposure is in general high for a developing country.